Systemic life cycle design error reduction model for construction and engineering projects - Love, Peter; Edwards, David; Smith, Jim (Taylor & Francis, 2013)
Design errors have resulted in a plethora of catastrophic building and engineering failures, and some cases have caused death and injury to workers and members of the public. Despite continued efforts to improve project performance, errors remain a significant problem due to recurrent error- traps that prevail at the people, organisational and project levels. In addressing the need to reduce error, a systemic model that is grounded in practice and the aggregated views of 46 practitioners who were interviewed about the nature and prevention of design errors is proposed. The developed model can be used to identify and mitigate design errors as well as stimulate learning throughout a project's life cycle.